Delineating the effect of upward propagating migrating solar tides with the TIEGCM-ICON - Maute, Astrid; Forbes, Jeffrey M.; Cullens, Chihoko Y.; Immel, Thomas J. (Frontiers in Astronomy and Space Sciences, 2023)
The vertical coupling of the lower and upper atmosphere via atmospheric solar tides is very variable and affects the thermosphere and ionosphere system. In this study, we use Ionospheric Connection (ICON) explorer data from 220-270 Day Of Year (DOY), 2020 when large changes in the migrating semidiurnal tide (SW2) and the zonal and diurnal mean (ZM) zonal wind occur within 8 days. We use the ICON Level4 product, the thermosphere-ionosphere-electrodynamics general circulation model (TIEGCM) driven by tides fitted to ICON observations via the Hough Mode Extension (HME) method. The effect of the upward propagating tides is isolated by examining the difference between two TIEGCM simulations with and without tidal HME forcing at the model lower boundary. The simulations reveals that the solar SW2 changes its latitudinal structure at 250 km after DOY 232 from two peaks at mid latitudes to one broad low latitude peak, while at 110 km the two-peak structure persists. The ZM zonal wind at 250 km undergoes a similar large change. These SW2 changes are associated with the prevalence of antisymmetric HMEs after DOY 232. The migrating diurnal, terdiurnal and quaddiurnal tides at 250 km undergo similar variations as SW2. TW3 is strong in the thermosphere and most likely caused by nonlinear tidal interaction between DW1 and SW2 above 130 km. Surprisingly, the solar in-situ forcing of TW3 and SW2 in the upper thermosphere is not nearly as important as their upward propagating tidal component. Associated with the strong dynamical changes, the zonal and diurnal mean NmF2 decreases by approximately 15-20%, which has a major contribution from the O/N_2 decrease by roughly 10%. These changes are stronger than general seasonal behavior. While studies have reported on the dynamical changes via SW2 in the mesosphere- lower thermosphere (MLT) region during the equinox transition period, this study is, to our knowledge, the first to examine the effects of rapid changes in SW2 on the upper thermosphere and ionosphere. The study highlights the potential of using ICON-TIEGCM for scientific studies.